Neurophysiological and cognitive enhancements in autonomous sensory meridian response identified using heart rate variability and electroencephalography connectivity - Wang, In-Nea; Kim, Hayom; Kim, Hakseung; Yoon, Ho-Jin; Park, Jun-Su; Kim, Jung Bin; Kim, Dong-Joo (Frontiers in Psychology, 2025)
IntroductionAutonomous sensory meridian response (ASMR) is a sensory-emotional phenomenon characterized by tingling sensations and relaxation, typically elicited by auditory or visual stimuli. Although anecdotal reports suggest potential cognitive and physiological benefits, empirical evidence remains limited. Furthermore, objective physiological monitoring of ASMR-related responses has yet to be systematically explored.MethodsTwenty healthy Korean adults underwent 5-min exposure to natural sound-based ASMR stimuli. Cognitive assessments, including the Trail Making Test Part B and a delayed word recall task, were administered before and after stimulation. Simultaneously, electroencephalography (EEG) and electrocardiography were recorded to examine power spectral density (PSD), functional connectivity (FC), and HRV indices. Gaussian Mixture Modeling (GMM) was applied to HRV features to classify responders.ResultsPost-ASMR stimulation, participants demonstrated significant cognitive improvements (Trail Making Test: P = 0.004; Delayed Recall: P = 0.022). EEG analyses revealed increased PSD in frontoparietal regions and enhanced FC, particularly in beta and gamma bands. HRV measures showed elevated parasympathetic activity. GMM clustering identified two groups; responders exhibited greater cognitive enhancement and FC changes than non-responders. Correlation analyses showed positive associations between HRV indices and memory performance, and a negative correlation between beta-band prefrontal FC and recall.DiscussionAuditory ASMR stimulation improves executive and memory functions, potentially through modulating neural connectivity and autonomic function. HRV indices serve as practical, non-invasive markers for real-time monitoring of auditory-induced neurocognitive changes, offering potential for personalized cognitive enhancement strategies.